Assessing the readiness of Malaysian construction industry towards construction 4.0 - Chia, Chi Wei (2024)
Industry 4.0 impacts all industries, and the construction industry is no exception. Hence, the emergence of “Construction 4.0” denotes a shift towards digitalisation tailored for the construction industry, triggering various governmental policy initiatives. The previous studies mainly focus on tools in enhancing single project areas. This research aims to investigate the adoption of Construction 4.0 digital tools in the Malaysian construction industry. The objectives are to identify the benefits incurred from adopting Construction 4.0 digital tools, to explore the barriers of implementing Construction 4.0 digital tools and to infer the readiness of Construction 4.0 digital tools by the construction industry players. A questionnaire survey gathered data from 171 respondents in Klang Valley, Malaysia, which underwent reliability analysis and various inferential tests such as Friedman Test, Chi-Square Test, KruskalWallis Test and Spearman’s Correlation Coefficient Test. There are 11 digital tools, 10 benefits, 14 barriers, and 6 strategies identified from the literature review and further analysed in this research. The result of the survey revealed that the top 3 recognised benefits incurred from adopting digital tools are “Precise design, measurement and documentation of my project are facilitated by using digital tools”, “Accident and injuries are minimised by using digital tools in my project” and “My workers feel safer working with digital tools on my project”. However, the findings uncovered a weak correlation between past digital tool adoption and future usage recommendations among respondents. This result can be attributed to three main barriers, high implementation cost, lack of expertise and skilled workers and lack of government support. Considering several factors such as inconsistent implementation of digital tools, varying adoption rates among professionals and companies, selective tool usage and adoption barriers for key players, it can be inferred that Malaysian construction industry players are not ready for Construction 4.0. Following that, there is a moderate to weak correlation between the strategies proposed and the barriers encountered. This conveys an important signal that no one-size-fits-all strategy can fully address a specific barrier. In short, collaboration among stakeholders is vital to overcoming barriers and enhancing the construction industry’s readiness for Construction 4.0.